2014
DOI: 10.1016/j.ceca.2014.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Calcium imaging of infrared-stimulated activity in rodent brain

Abstract: Summary Infrared neural stimulation (INS) is a promising neurostimulation technique that can activate neural tissue with high spatial precision and without the need for exogenous agents. However, little is understood about how infrared light interacts with neural tissue on a cellular level, particularly within the living brain. In this study, we use calcium sensitive dye imaging on macroscopic and microscopic scales to explore the spatiotemporal effects of INS on cortical calcium dynamics. The INS-evoked calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 40 publications
4
69
0
Order By: Relevance
“…The increase in free calcium caused by infrared irradiation was found in the vestibular system 13,15 in cardiomyocytes 14 and the cortex. 16,17 While it has been well documented that the intracellular calcium concentration increases upon irradiation, it is not clear how the increased calcium results in an action potential.…”
Section: Affecting the Calcium Homeostasismentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in free calcium caused by infrared irradiation was found in the vestibular system 13,15 in cardiomyocytes 14 and the cortex. 16,17 While it has been well documented that the intracellular calcium concentration increases upon irradiation, it is not clear how the increased calcium results in an action potential.…”
Section: Affecting the Calcium Homeostasismentioning
confidence: 99%
“…11,12 Other experiments demonstrated that IR increases the intracellular calcium concentration. [13][14][15][16][17][18] Recently, it has been demonstrated that the increase in intracellular calcium concentration results from a direct interaction of the radiation with intracellular calcium stores. 15 Pulse lengths for INS are typically 100 μs for cochlear stimulation and about 1 ms for peripheral nerve or cortical stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is currently only limited research focusing on interrogation of INS in cells of the central nervous system. One such study relied on calcium imaging to probe the visual cortex's response to INS and demonstrates a fast and slow component of the calcium signal [13], with another study showing that INS increased the spontaneous discharge rate of visual cortex neurons recorded in vivo in the Macaque through extracellular recordings of unit activity [14]. A similar study instead described the use of infrared light to cause neural inhibition [15].…”
Section: Introductionmentioning
confidence: 99%
“…16 Using Oregon Green dye as a calcium indicator, they observed wave-like propagation of the calcium signal following INS. The dynamics of the calcium signal consisted of a slow and a fast component.…”
Section: Ins Of the Central Nervous Systemmentioning
confidence: 99%
“…The Jansen group used electrophysiological recordings in combination with intrinsic optical calcium dye and flavoprotein fluorescence imaging in rodents to demonstrate the feasibility of INS application in the cortex, explore the optical parameters necessary for successful stimulation, and determine which cell types are affected by INS. 16,17 Intrinsic optical signal imaging is a technique used to detect local changes in blood flow via red light reflectance due to focal metabolic changes. 18 It is a convenient way to detect cortical activation patterns because it requires no contrast agent and can be used to image a relatively wide area (tens of square millimeters) with a resolution of the order of 10 microns.…”
Section: Ins Of the Central Nervous Systemmentioning
confidence: 99%